2002
DOI: 10.1159/000057877
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Urticaria, a New Pathogenic Concept: Hypohidrosis due to Interference with the Delivery of Sweat to the Skin Surface

Abstract: Background: Acetylcholine has been suspected to be a pathogenetic factor for cholinergic urticaria (CU), without definite evidence. In contrast, there are scattered reports of CU associated with acquired generalized hypohidrosis. We have recently examined 2 patients with CU in both of whom we noticed the presence of extensive hypohidrosis that occurred only in winter. Objective: In these 2 patients, acquired hypohidrosis due to superficial obstruction of the acrosyringium was suspected as the cause. Both case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 12 publications
0
52
0
2
Order By: Relevance
“…It has been reported that biopsy specimens from skin lesions show infl ammatory infi ltrates, including lymphocytes, neutrophils, and occasionally eosinophils around vessels and skin appendages [3,[21][22][23]. Winkelmann [21] reported that four CU patients showed infi ltrates around their hair follicles, whereas four others had infi ltrates around their sweat ducts.…”
Section: Abnormal Findings In Cholinergic Urticariamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that biopsy specimens from skin lesions show infl ammatory infi ltrates, including lymphocytes, neutrophils, and occasionally eosinophils around vessels and skin appendages [3,[21][22][23]. Winkelmann [21] reported that four CU patients showed infi ltrates around their hair follicles, whereas four others had infi ltrates around their sweat ducts.…”
Section: Abnormal Findings In Cholinergic Urticariamentioning
confidence: 99%
“…In a report of the literature that summarized cases with both CU and acquired anhidrosis/hypohidrosis, 12 of 16 patients with AIGA were suggested to be associated with CU [22]. Kobayashi et al [23] showed that biopsy specimens from two patients with both CU and AIGA showed an occlusion of the superfi cial acrosyringium and a lymphocytic infi ltration around the upper sweat duct. They proposed that the occlusions and subsequent leakage from the sweat ducts are responsible for the development of CU associated with anhidrosis.…”
Section: Association Of Anhidrosis With Cholinergic Urticaria and Posmentioning
confidence: 99%
“…Among cases of anhidrosis, AGA is rare [13,15,22,23,24,25,26,27,44,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65] (table 3). A total of 37 previous cases of AGA with detailed clinical features were identified in the English language literature as far as we could determine.…”
Section: Discussionmentioning
confidence: 99%
“…Otra hipó-tesis sugiere que podría existir un componente inmunológico contra el sudor con la producción de anticuerpos IgE, lo cual se ha podido comprobar por la reacción cutánea que ocurre en estos pacientes con la inyección de su propio sudor diluido (47). En algunos estudios japoneses se ha clasificado la urticaria colinérgica en cuatro grupos: urticaria colinérgica con oclusión de poros, urticaria colinérgica con hipohidrosis, urticaria colinérgica con alergia contra el sudor y urticaria colinérgica idiopática (48).…”
Section: Urticaria Colinérgicaunclassified